Mehrsprachigkeit. Defizit oder Potenzial? Nationalideologische Hindernisse im Sprachlernumfeld der dänischen Minderheit in Südschleswig - Frebel, Daniel; Steenberg Reyhé, Rune (Linguistik Online, 2016)
This paper examines language learning in the schools of the Danish minority in northern Germany. The paper shows that the pedagogic approach shaped along a historical narrative of Danish national ideology reflected both in the curriculum and the actual teaching practice, negatively influences the students’ language learning. Based on 14 in-depth interviews, participant observation and a deep cultural knowledge of the region and the institutions examined, we develop the following hypothesis. The ideological constraints connected to the minority’s position in the Danish national-historical narrative prevent the students' special learning conditions as non-native Danish speakers outside of Denmark from being taken sufficiently into consideration. The students, in a national spirit, are essentially measured by native standards, which most of them have no chance of living up to. This leads to a constant feeling of deficiency in connection with the Danish language on the part of the students and thus an alienation from it. It further has the feedback-effect of limiting both their language learning and further academic performance. We conclude that the specific plurilingual background of the learners needs to be taking into consideration, and reflected on by both teachers and students themselves by focusing the teaching practice and curriculum on communication, understanding and self-reflexion. This calls for a more pluralistic, flexible and pragmatic conceptualization of language as a tool shaped by social power relations and an emancipatory reflexion of the students' own position, challenges and choices in this constellation, both of which we argue are of high political rele-vance way beyond the German-Danish border region.